Impact of Medicaid expansion and state-level racial diversity on breast cancer endocrine therapy prescriptions: A quasi-experimental, comparative interrupted time series study. (March 2022) - Li, Chenghui; Najarian, Matthew; Halpern, Michael T.
Highlights: Medicaid expansion was associated with significant increases in ET prescriptions in expansion vs. nonexpansion states. Differences in ET prescriptions between expansion and nonexpansion states was only observed among racially more diverse states. The gaps between racially more diverse nonexpansion and expansion states significantly widened after expansion. Abstract: Aims: To determine whether Medicaid expansion impacted racially more diverse states similarly as racially less diverse states in endocrine therapy (ET) prescriptions. Methods: A quasi-experimental, comparative interrupted time series study of Medicaid-financed ET prescriptions from 2011 to 2018 Medicaid State Drug Utilization Database. The exposures were state's Medicaid expansion and racial diversity status. The outcome was state's quarterly number ET prescriptions per 100, 000 non-elderly adult females (NAFs). Results: During the year of expansion, ET prescriptions increased sharply in expansion states but remained flat in nonexpansion states (slope: 11.96 vs. 0.43 prescriptions per 100, 000 NAFs per quarter, p < 0.001). After that, the slopes were similar between expansion and nonexpansion states (1.75 vs. 0.24, p = 0.057) but the level of prescriptions in expansion states maintained at a higher level. When stratified by state's racial diversity status, the slope of increase in the first year was sharper for racially more diverse expansion states (16.49, p = 0.008) than racially less diverse expansion states (8.46, p < 0.001), resulting in significant differences in ET prescriptions between racially more diverse expansion and nonexpansion states but largely nonsignificant differences between racially less diverse expansion and nonexpansion states. Conclusions: Although Medicaid expansion significantly increased ET prescriptions in expansion vs. nonexpansion states, this difference was only observed among racially more diverse states. Racially more diverse nonexpansion states had the lowest rates of ET prescriptions and the gaps from racially more diverse expansion states significantly widened after expansion. Policy summary: Our study shows that, before expansion, racially more diverse nonexpansion states had the lowest rates of ET prescriptions. After expansion, the gaps between these states and racially more diverse expansion states significantly widened. These results highlighted the importance of continuing to examine the health impacts of states not expanding Medicaid, including the health equity impacts for low income racial/ethnic minority populations with cancer and other life-threatening diseases.